Does convective aggregation need to be represented in cumulus parameterizations?. (2nd October 2013) - Tobin, Isabelle; Bony, Sandrine; Holloway, Chris E.; Grandpeix, Jean‐Yves; Sèze, Geneviève; Coppin, David; Woolnough, Steve J.; Roca, Rémy
<x xml:space="preserve">Abstract</x> [1] Tropical deep convection exhibits a variety of levels of aggregation over a wide range of scales. Based on a multisatellite analysis, the present study shows at mesoscale that different levels of aggregation are statistically associated with differing large‐scale atmospheric states, despite similar convective intensity and large‐scale forcings. The more aggregated the convection, the dryer and less cloudy the atmosphere, the stronger the outgoing longwave radiation, and the lower the planetary albedo. This suggests that mesoscale convective aggregation has the potential to affect couplings between moisture and convection and between convection, radiation, and large‐scale ascent. In so doing, aggregation may play a role in phenomena such as "hot spots" or the Madden‐Julian Oscillation. These findings support the need for the representation of mesoscale organization in cumulus parameterizations; most parameterizations used in current climate models lack any such representation. The ability of a cloud system‐resolving model to reproduce observed relationships suggests that such models may be useful to guide attempts at parameterizations of convective aggregation.